The Intersection of Religion and Pancasila in Dalihan Na Tolu - Husna Amin; Nanda Saputra; Desi Asmaret (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2022)
Humans' characteristics as social beings and God-created creatures are shaped by culture's past.) As long as there is life, culture will never disappear. Genoside occurs when the state commits ethnic massacres, inter-ethnic conflicts, inter-religious conflicts, and so forth. The diverse South Tapanuli community is relatively active, and kinship relationships are highly mobile. Descriptive qualitative research is used in this study. In order to keep the dalihan na tolu community strong and united, some disputes should go through mediation instead of the courts. The authority to control the land over communal land rights belonged to indigenous people in the ulayat lands of the Harahap, Siregar, and other clans, such as the Dalimunthe, Daulay in Angkola. If the land is not used, it will once again be a communal right that is protected by the Angkola Batak indigenous people's village heads and/or customary holders. The act of selling and buying rights causes these activities to become deviant.In order to strengthen indigenous peoples and ulayat lands in the future, cooperation is required. In order to keep the dalihan na tolu community strong and united, some disputes should go through mediation instead of the courts.